DESAIN PRODUK MANDI, CUCI, KAKUS (MCK) DI WILAYAH PASCA BENCANA BANJIR (Studi Kasus: Jakarta Timur) - Indah Fitriana Hapsari (Universitas Mercu Buana, 2020)
Activities inside the bathroom have already been a part of human activities every day. Because of that bathroom became one of the most visited places. From the function point of view, a bathroom is a place to cleaning ourselves self (clean up), so the most crucial requirement for the bathroom is to serve clean and freshwater. Regarding its function as a place to cleaning ourself, room arrangement needs to be associated with bathroom need. Inside a bathroom, there is a need for space for human movements, such as to rub the body, pour, and dry ourselves. So, to design a qualified bathroom, have to be concerned about all the needs, then the excellent bathroom can be developed and useful for everyone.